A Location specific and Trends based Video Streaming Platform with integrated Web Speech API through Angular 6 - Kadam, Amol K; Patil, T.B; Kesharwani, Yash; Garg, Harsh; Gupta, Akash (International Journal of Computer Sciences and Engineering, 2019)
Online video search and play is an aspect of that is used for innumerable purposes which comprise infotainment, video-logs, advertisement, endorsement, etc. It is one of the most resource intensive processes. Using up-to-date technologies to create an application to improve both user experience and application performance is important so as to adapt with the changes like hardware capability, bandwidth speeds and software platforms. To attract users from conventionally used platforms to newer ones we utilize the latest Angular v6 framework for creating a cross platform single page application (load once and refresh dynamically mechanism) which can be developed on a component and service driven model using any popular programming language along with the features like voice enabled search through integration of open source web speech API for real time voice recognition and content filtering based on trend, geographic location and other statistics. To create such application the primary need is to avail it with vast amount of organised data that can be easily accessed; a suitable data API like YouTube API can seamlessly be used with the application. This web application is highly responsive with support for mobile devices like tablets and smartphones. It can be easily morphed as the technologies advances, newer versions Angular provides facility to extend older versions with features introduced with them. The proposed application has the potential to be extended by adding other APIs to suit user’s need and expand our application’s database by adding more than one source for videos through integration of multiple data API.